2014
DOI: 10.1073/pnas.1407122111
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a nematode-infecting virus

Abstract: Orsay, the first virus discovered to naturally infect Caenorhabditis elegans or any nematode, has a bipartite, positive-sense RNA genome. Sequence analyses show that Orsay is related to nodaviruses, but molecular characterizations of Orsay reveal several unique features, such as the expression of a capsid-δ fusion protein and the use of an ATG-independent mechanism for translation initiation. Here we report the crystal structure of an Orsay viruslike particle assembled from recombinant capsid protein (CP). Ors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…The crystal structure of the Orsay capsid shows that the C-terminus of the Orsay CP is tucked underneath of a tightly bound trimeric spike [23] (S8 Fig). Therefore, for a trimeric fiber to form, the polypeptide sequence would have to go around the timeric spike from outside, spanning a distance of at least 60-Å in order to reach the 3-fold axis.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of the Orsay capsid shows that the C-terminus of the Orsay CP is tucked underneath of a tightly bound trimeric spike [23] (S8 Fig). Therefore, for a trimeric fiber to form, the polypeptide sequence would have to go around the timeric spike from outside, spanning a distance of at least 60-Å in order to reach the 3-fold axis.…”
Section: Discussionmentioning
confidence: 99%
“…Structural features around the 3-fold axis are diverse in Nodaviridae-like and Tombusviridae-like viruses. In MCTV, grouper nervous necrosis virus (GNNV) (19), and Orsay virus (20), three N-arms form a trident structure as described above (18-20) ( Fig. 7E, Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Several unique characteristics of these nematode viruses have suggested that they represent a new and distinct group of nodavirus-like pathogens. For one, the OV capsid structure is more similar to that of piscine betanodaviruses than that of alphanodaviruses (36,37). Furthermore, although these nematode viruses encode an RdRP and capsid protein (CP) on RNA1 and RNA2 segments, respectively, they also encode an additional ORF downstream of the CP on RNA2 called ␦ that is unrelated to any known protein, and these viruses also do not encode the subgenomic (RNA3) segment typically found in nodaviruses (13,38).…”
Section: Nonnatural Virus Models (I) Flock House Virusmentioning
confidence: 99%